Internal Marketing and Employee’s Innovative Work behaviour; Examining the Moderating Effect of Personality Traits - Madiha Mahfooz; Iqrar Hussain; Muhammad Nasir; Sabir (International Journal of Business and Economic Affairs, 2023)
This study highlights the influence of personality on internal marketing linked to innovativeness in a business. Internal marketing and Innovative work behavior includes wide range of processes as well as activities associated toward sensory reactions, perceptions, attitude formation, preferences, decisions, satisfaction evaluation and loyalty formation of employees. Employee’s behaviors are influenced by exogenous and endogenous factors. Exogenous factors include attributes associated with employees and environmental influences. Endogenous factors include characteristics of employees. Data carried out through 300 questionnaires from Employees of banks in Rawalpindi, Islamabad and AJK. The data was analyzed utilizing OLS regression technique. The findings indicate that the innovative work behaviour of employees significantly increase internal marketing. Moreover, moderating role of big five personality traits plays significant role to promote internal marketing. The results of this study would enable companies to retain customers for long run. It is useful for academic researchers and practitioners engaged in marketing.